Being Responsible: How Managers Aim to Implement Corporate Social Responsibility. Issue 7 (September 2020) - Hunoldt, Michael; Oertel, Simon; Galander, Anne
Focusing on the corporate social responsibility (CSR) implementation process, we analyze how institutional complexity that arises from tensions between social and environmental elements and economic and technical concerns is managed by CSR managers. We further question how these micro-level processes interact with organizational-level processes over time. Our research is a 24-month qualitative process study in which we followed CSR managers. The study's results allow us to distinguish between four strategies that CSR managers use to promote CSR implementation and to cope with tensions. Our results further indicate that organizational characteristics influence the intensity with which these strategies are applied and that the intensity of strategy application affects organizational behavior in the course of time. Through the discussion of these findings, our study contributes to the research on micro-level processes that occur in response to complex institutional demands as well as to the development of a comprehensive, multilevel approach to CSR implementation.